Anthocyanin extract from black rice attenuates chronic inflammation in DSS-induced colitis mouse model by modulating the gut microbiota - Li Yanmei; Yuan Fahu; He Xiaohong; Fu Shaohua; Fan Bolin (Open Chemistry, 2023)
There is substantial evidence for the probiotic activity of anthocyanins, but the relationship between anthocyanins involved in the regulation of microbiota and intestinal inflammation has not been fully elucidated. The aim of this study was to investigate the regulatory effects of black rice anthocyanin extract (BRAE) on intestinal microbiota imbalance in mice with dextran sulfate sodium (DSS)-induced chronic colitis. DSS was added into drinking water to induce a mouse model of chronic experimental colitis, and BRAE was given by gavage (200 mg/kg/day) for 4 weeks. Body weight, fecal viscosity, and hematochezia were monitored during administration. After mice were sacrificed, the serum concentrations of TNF-α and IL-6 were detected by enzyme-linked immunosorbent assay, and the composition of intestinal flora was analyzed by 16S rDNA sequencing. The results showed that BRAE significantly suppressed DSS-induced colonic inflammatory phenotypes and maintained colon length in mice. In addition, BRAE reduced intestinal permeability and improved intestinal barrier dysfunction in mice with colitis. Gut microbiota analysis showed that BRAE significantly improved the imbalance of intestinal microecological diversity caused by DSS, inhibited the increase in the relative abundance of inflammatory bacteria, and promoted the abundance of anti-inflammatory probiotics including Akkermansia spp.